1983
DOI: 10.1677/joe.0.0970243
|View full text |Cite
|
Sign up to set email alerts
|

Plasma somatomedin-C in fasted and refed rats: close relationship with changes in liver somatogenic but not lactogenic binding sites

Abstract: Circulating levels of somatomedins in man and rats are reduced by fasting and restored by refeeding. To determine the mechanisms for these alterations in somatomedin levels, the affinities and binding capacities of 125I-labelled bovine GH (somatogenic binding sites) and of 125I-labelled ovine prolactin (lactogenic binding sites) were assessed in liver homogenates from fasted and refed rats. Correlations were made with plasma immunoreactive somatomedin-C (Sm-C) and plasma insulin.During fasting and refeeding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
2
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(78 citation statements)
references
References 25 publications
5
70
2
1
Order By: Relevance
“…In many experimental models food restriction is associated with reduced skeletal growth, with such association primarily resulting from impaired growth hormone action (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In a previous study we demonstrated that mice undergoing 4 weeks of food restriction exhibited increased expression of Fgf21 (both in the liver and in the growth plate), growth hormone (GH) 3 insensitivity, and a concomitant reduction of their body linear growth and growth plate chondrogenesis (17).…”
mentioning
confidence: 99%
“…In many experimental models food restriction is associated with reduced skeletal growth, with such association primarily resulting from impaired growth hormone action (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In a previous study we demonstrated that mice undergoing 4 weeks of food restriction exhibited increased expression of Fgf21 (both in the liver and in the growth plate), growth hormone (GH) 3 insensitivity, and a concomitant reduction of their body linear growth and growth plate chondrogenesis (17).…”
mentioning
confidence: 99%
“…Fasting appears to decrease GU binding in the liver because of redueed numbers of GH receptors (Maes ~ al., 1983;1984a;1984b to promote growth (Thissen ~~, 1990). A zinc deficient rat is not in a state of nutritional sufficiency.…”
Section: Ippbct Op B~ Growtb Borkobmentioning
confidence: 99%
“…A reduction of GH binding in liver has been observed in rats [17,37], cattle [4] and sheep [2]. It has also been reported that feed restriction decreases GHR mRNA levels in the liver of young pigs [9], whereas it increases these levels in peripubertal gilts [7].…”
Section: Discussionmentioning
confidence: 93%